The kinematics of paretic lower limb in aquatic gait with equipment in people with post-stroke hemiparesis - Pereira J.A.* (2019)
© 2019 Elsevier LtdBackground: Devices are commonly used in aquatic gait rehabilitation; therefore, investigating the effect of these devices is important. We evaluated the combined use of buoyancy cuffs and ankle weights during aquatic gait on paretic leg kinematics in people with hemiparesis. Methods: Fifteen adults (58.6 ± 4.8 years) in the chronic phase post-stroke walked on a 4.5 m walkway with underwater immersion at the height of the xiphoid process in five conditions: (1) without equipment; (2) with ankle weights or (3) buoyancy cuffs on both legs; (4) with a buoyancy leg cuff on the non-paretic leg and an ankle weight on the paretic leg; (5) with an ankle weight on the non-paretic leg and a buoyancy leg cuff on the paretic leg. Five trials were performed for each condition for a total of 25 trials and the kinematic data were recorded. Analysis of covariance was used with walking velocity as a covariate to analyze spatiotemporal and angular variables of the paretic leg. Findings: The condition with buoyancy cuff on the paretic leg increased (~20°) the maximum angle of knee flexion in the mid-swing phase compared to that seen with weights on both legs or weight on the paretic leg. Buoyancy cuffs on the paretic leg increased the step length by 5.6 cm. The ankle weights on the paretic leg condition increased the total (6%) and single support (4%) duration compared to that seen with a buoyancy cuff on the paretic leg. Interpretation: Aquatic gait with buoyancy cuffs on both legs or on the paretic leg can modify gait kinematics compared to that with weight on both legs or on the paretic leg. Long term effects of training with those conditions needs further research.